Perceived Effects of Interpersonal Conflicts among Nurses at Tertiary Care Hospital, Lahore : Interpersonal Conflicts among Nurses - Naeem, Asra; Zafar, Misbah; Farooq, Qandeel; Philips, Sehrish; Ejaz, Marriam; Sadiq, Parsikla; Arshad, Kanza (Pakistan Journal of Health Sciences, 2023)
Interpersonal conflicts at workplace are not uncommon, it affects the nurses physical and mental health. It creates highly-stress environment and affects quality of patient outcomes. It poorly affects job performance and increases turnover. It creates disputes among nurses and leads to work disruptions. Objective: To examine perceived effects of interpersonal conflicts among nurses Methods: The quantitative descriptive study design and simple random sampling technique was used in this study. Demographic data from the study reveals 187 participants from which data were collected that indicates majority of the participants were 136 females. Only 33.7% of nurses reported that they were treated with love and kindness. However, 28.3% showed sometimes nurses had been faced with excessively harsh criticisms about my work. Results: The participants of this study include 83.4% nurses are Muslim and 16.6% are Christian. 70.6% nurses have 1 to 3 years’ experience, 15.5% nurses have 3 to 5 years’ experience and 13.9% have >5 years’ experience. Conclusions: However, the results of this study could help to aware nurses about workplace conflicts and strategies that promote to reduce conflicts at workplace among nurses.